Arabic language efficacy questionnaire (ALEQ): assessing self-efficacy and achievement - Nik Hanan Mustapha,; Nik Farhan Mustapha,; Nadwah Daud,; Mahmud Abd Wahab, (Penerbit UKM, 2013)
Self-efficacy has long been a focus in language learning. Perceived as one’s belief in his or her own capabilities in accomplishing a particular task, it affirms that personal behaviours, thoughts, beliefs and environmental conditions pose great impact on achievement. However, in Arabic language learning, research on self-efficacy is still at its infancy, what more of an instrument which precisely measures self-efficacy in Arabic language learning environment. Hence, this paper aims at verification of a newly-developed instrument, Arabic Language Efficacy Questionnaire (ALEQ), as well as to explore the relationship between self-efficacy and Arabic language achievement. A sample of 234 undergraduate students majoring in Arabic language was exposed to ALEQ, and a set of tests to determine their achievement in reading, writing and grammar. A principal components analysis with varimax rotation yields a 3-factor solution with satisfactory psychometric properties. The Pearson’s r correlation analysis revealed a positive correlation between efficacy in reading, writing and grammar and students’ achievement. Results clearly document that the ALEQ is a multidimensional measurement of Arabic language efficacy. It is concluded that although ALEQ has broad applicability, the scale herein may have relevance to the students’ level of confidence in learning Arabic language and may be used in both research and teaching environments.